The effect of Concentration of Milk Powder and Gelatine on the Quality of Purple Sweet Potato Extract Probiotic Drink - Nurliana Manurung; Sentosa Ginting; Era Yusraini (Universitas Sumatera Utara, 2013)
The aim of this research was to find the effect of Concentration of Milk Powder and Gelatine on the Quality of Purple Sweet Potato Extract Probiotic Drink. This study was conducted to determine the concentration of milk powder and gelatine to manufacture probiotic drink from extract of purple sweet potato, and to introduce the products of purple sweet potato extract. The research was conducted in Oktober-Desember 2012 in the Laboratory of Food Technology, Faculty of Agriculture, USU, Medan, used a completely randomized design with two factors : the concentration of milk powder (5%, 7%, 9% and 11%) and the concentration of gelatine (0,3%, 0,4%, 0,5% and 0,6%). The parameters analyzed were total lactic acid, total soluble solid, pH, total microbe, protein content, the value of the color score, the value of viscosity score, and organoleptic values of color, aroma and flavor. The results showed that the concentration of milk powder had highly significant effect on total lactic acid, total soluble solid, pH, total microbe, protein content, the value of the color score, the value of viscosity score, and organoleptic values of color, aroma and flavor. The concentration of gelatine had significant effect on the pH and had highly significant effect on protein content and the value of viscosity score. The interaction of the two factors had highly significant effect on protein content and had significant effect on the value of viscosity score. The concentration of milk powder of 11% and concentration gelatine of 0,5% produced the best quality of purple sweet potato extract probiotic drink. . Key words : Gelatine, Milk Powder, Probiotic Drink, Purple Sweet Potato Extract